Marital Relationship and Tactics of Conflict Resolution between Couples - Bolze, Simone Dill Azeredo; Schmidt, Beatriz; Crepaldi, Maria Aparecida; Vieira, Mauro Luís (Actualidades en Psicología, 2013)
This research aims to characterize the marital relationship and tactics of conflict resolution between couples. The participants were 104 couples from a state located in the south of Brazil, totaling 208 respondents. The average age of the women was 33.27 years old and men 36.45. The time of conjugal union ranged from one year to 27 years and the average was 10.74. The measurements used were: a questionnaire to characterize the marital relationship and the Revised Conflict Tactics Scales (CTS2). The results obtained by means of statistical analyzes suggest that most couples consider to experience a harmonic conjugal relationship with preponderance of negotiation strategies in emergency cases of marital conflict. However, attitudes involving psychological aggression also appeared as forms of conflict resolution. The results contribute to elucidate the inter-relational dynamics of healthy marriages.